TINJAUAN HUKUM TERHADAP KONTRAK JUAL-BELI KARET PADA PERUSAHAAN PTPN III MEDAN ( Riset Pada PTPN III MEDAN ) - ANDRIANA SISKA DEVI S (JURNAL CIVIL LAW USU, 2013)
ABSTRAK : In of globalization era many needs that must be met by the public, resulting in the smooth flow of trading, along with the contract / purchase agreement. Especially in the automotive industry sectors that require natural rubber as the staple manufacture of tires and sperpart. Therefore, the company PTPN III field that serves as one part of the State-Owned Enterprises (SOEs), which are in North Sumatra can take part by greater utilization of this state. Issues raised in this paper is how the application of Article 1320 Civil Code on the terms - a legal requirement of the contract of sale contract PTPN III field with its trading partners, how the system or mode of payment adopted by the company PT. Perkebunan Nusantara III field with trading partners and how the solution in the event of a default of one party to a contract of sale is rubber. The research method used in writing this paper is a descriptive normative, ie research that refers to legal norms and its done by doing surveys to the field to get the information that will be supported on existing theories of data collection by research library (Library Research), which conducted a study using data from a variety of reading materials, such as legislation, books, and internet are considered relevant to the topic. In addition, research conducted field (Field Research) to conduct research into the field to get the facts, that is by interviewing the relevant parties. Rubber sales contract on PT. Perkebunan Nusantara III field with its trading partners in accordance with the terms of a valid contract set forth in Article 1320 Civil Code, as evidenced by the agreement of the parties to a contract, determine the price of payment and delivery of goods, as well as the type of goods / objects clearly and be done with the sole purpose of to meet the needs of the parties. In the event of a default (broken promises) made by one party to a contract of sale which resulted in disputes in both parties, the contract may be canceled and also included fines. But it would do the negotiation / consultation beforehand and wear Arbitration means if the first way is no solution. The word keys: contract, purchase and sale, PTPN II.7